PENGGUNAAN METODE KAUNY QUANTUM MEMORY UNTUK MENINGKATKAN HASIL BELAJAR MATA PELAJARAN BAHASA ARAB KELAS 4 MI Ya BAKII KESUGIHAN 01 - Risma Makhafsi; Nani Kurniasih (EL ROBIH: Jurnal Pendidikan Madrasah Ibtidaiyah, 2024)
This research aims: this type of research uses Classroom Action Research. The location of this research was carried out at MI Ya BAKII Kesugihan 01, which was carried out in August-September 2022. The subjects of this research were class 4.03 students and class 4.04 students at MI Ya BAKII Kesugihan 01, totaling 54 students. Data collection techniques were carried out using interviews, observation and tests. The instrument testing technique uses validity and reliability tests. Data analysis techniques use qualitative techniques and quantitative techniques. The research procedures were carried out into Pre-Cycle, Cycle I, Cycle II and each cycle had four stages, namely planning, implementation, observation and reflection. Based on the results obtained, students in class 4.02 and class 4.03 have experienced an increase in learning outcomes for Arabic language subjects, namely in the pre-cycle implementation, in class 4.02 there were 17 students who passed the KKM with a percentage of 58.6% and in class 4.03 there were 15 students who passed the KKM with a percentage of 55.5%. In the implementation of cycle I, in class 4.02 there were 21 students who passed the KKM with a percentage of 72.4% and in class 4.03 there were 18 students who passed the KKM with a percentage of 66.6%. In the implementation of cycle II, in class 4.02 there were 27 students who passed the KKM with a percentage of 93% and in class 4.03 there were 24 students who passed the KKM with a percentage of 88.8%.